Helping someone cope with grief - Don, Yahya (malaysiandigest.com . All rights reserved., 2011)
Losing someone close to you is very painful and the pain may take a long time to 'heal'.With the loss various emotions such as shock, anger and guilt may follow.It is common for a person in this situation to feel helpless, awkward and unsure.When talking to them, we are scared of saying the wrong things which could make the person feel even worse.In most instances, people feel that there is little that they can do in order to make things better for someone who is in 'grieving'.According to Helpguide.org, while someone could not take away the pain of the loss, they can provide the much-needed comfort and support. This may start by letting the person know that you care.